Analyzing Social Media Network For Students In Presidential Election 2019 With NODEXL - Irwan Dwi Arianto (Jurnal Ilmu Komunikasi, 2019)
Twitter is widely used in digital political campaigns. Twitter as a socialmedia that is useful for building networks and even connecting politicalparticipants with the community. Indonesia will get a demographic bonus startingnext year until 2030. The number of productive ages that will become ademographic bonus if not recognized correctly can be a problem. The electionorganizer must seize this opportunity for the benefit of voter participation. Thisstudy aims to describe the network structure of students in the 2019 presidentialelection. The first debate was held on January 17, 2019 as a starting point for dataretrieval on Twitter social media. This study uses data sources derived from Twittertalks from 17 January 2019 to 20 August 2019 with keywords “#pilpres2019 OR#mahasiswa since: 2019-01-17”. The data obtained were analyzed by thecommunication network analysis method using NodeXL software. Our Analysisfound that Top Influencer is @jokowi, as well as Top, Mentioned also @jokowiwhile Top Tweeters @okezonenews and Top Replied-To @hasmi_bakhtiar. Jokowiis incumbent running for re-election with Ma’ruf Amin (Senior Muslim Cleric) ashis running mate against Prabowo Subianto (a former general) and Sandiaga Unoas his running mate (former vice governor). This shows that the more concentratedin the millennial generation in this case students are presidential candidates@jokowi. @okezonenews, the official twitter account of okezone.com (MNC MediaGroup). Hasmi Bakhtiar (@hasmi_bakhtiar) is a graduate student at the Universityof Lille in France from Indonesia who often criticizes the Jokowi government.